Perinatal manifestations of congenital disorders of glycosylation—A clue to early diagnosis - Greczan, Milena; Rokicki, Dariusz; Wesół-Kucharska, Dorota; Kaczor, Magdalena; Rawiak, Agata; Jezela-Stanek, Aleksandra (Frontiers in Genetics, 2022)
N-glycosylation defects—isolated or mixed with other glycosylation defects—are the most frequent congenital disorders of glycosylation and present mostly in childhood, with a specific combination of non-specific phenotypic features. The diagnosis, however, is often delayed. The aim of this study is to describe the perinatal phenotype of congenital disorders of N-glycosylation. We present an analysis of perinatal symptoms in a group of 24 one-center Polish patients with N-glycosylation defects—isolated or mixed. The paper expands the perinatal phenotype of CDGs and shows that some distinctive combinations of symptoms present in the perinatal period should raise a suspicion of CDGs in a differential diagnosis.